An Assessment of Program Eligibility Among Participants in Day Reporting Centers - Mowbray, Orion (International journal of offender therapy and comparative criminology, 2023)
Day reporting centers (DRCs) vary considerably in how participant eligibility is determined and to date, there is little to no knowledge whether criteria for DRC eligibly are appropriately applied in program entrance. This study examines a statewide sample of individuals in community supervision settings and compares DRC eligibility criteria between DRC and non-DRC participants to examine differences between DRC participants and non-participants. Using a propensity score matched sample of 1,554 participants, study findings suggest that DRC participants show higher risk, need, and responsivity factors, consistent with the DRC programing model. These results suggest many individuals appear to be appropriately matched to DRCs, which may in turn, may influence their likelihood of program success, among other factors.